2017
DOI: 10.1080/20008198.2017.1351219
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioral therapy for the treatment of PTSD

Abstract: Background: A variety of therapeutic approaches have been implemented to treat post-traumatic stress symptoms and concomitant difficulties. Those interventions focusing on trauma are considered first-line treatment for children and adolescents. Trauma Focused Cognitive Behavioral Therapy (TF-CBT, Cohen, Mannarino & Deblinger, 2006), and a similar type of group intervention, the Cognitive Behavioral Intervention on Trauma in Schools (CBITS, Stein et al., 2003), have received the most empirical support through r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Relative to an assessment-only control condition, telephone-administered CBT reduced PTSD symptoms and overall distress among people who underwent stem cell transplants (Duhamel et al, 2010). However, in another study (Freedman et al, in press; reviewed in Roberts et al, 2019), telephone-delivered CBT started within three months of trauma exposure was no better than treatment-as-usual in reducing acute PTSD symptoms. Research on patient acceptability, comfort, and preferences regarding telephone-based therapy is limited, but telephone care appears to be acceptable as other modalities (Cuijpers, Noma, Karyotaki, Cipriani, & Furukawa, 2019).…”
Section: Patient Process Comfort and Preference In Clinical Video Tel...mentioning
confidence: 95%
“…Relative to an assessment-only control condition, telephone-administered CBT reduced PTSD symptoms and overall distress among people who underwent stem cell transplants (Duhamel et al, 2010). However, in another study (Freedman et al, in press; reviewed in Roberts et al, 2019), telephone-delivered CBT started within three months of trauma exposure was no better than treatment-as-usual in reducing acute PTSD symptoms. Research on patient acceptability, comfort, and preferences regarding telephone-based therapy is limited, but telephone care appears to be acceptable as other modalities (Cuijpers, Noma, Karyotaki, Cipriani, & Furukawa, 2019).…”
Section: Patient Process Comfort and Preference In Clinical Video Tel...mentioning
confidence: 95%
“…Numerous studies have highlighted the effectiveness of CBT for PTSD in children and adolescents exposed to various traumatic experiences [5,10,17,[40][41][42][43]. During CBT, therapists educate youths on stress reduction techniques, leading to the individual's preparedness to gradually expose himself/herself to and, therefore, gain mastery over the trauma stimuli.…”
Section: Cbt For the Treatment Of Ptsd In Children And Adolescentsmentioning
confidence: 99%
“…Trauma-focused-cognitive behavioral therapy (TF-CBT) is the most widely used and bestresearched manual-based CBT protocol for PTSD [8][9][10], whereas Cognitive Behavioral Intervention for Trauma in Schools (CBIΤS) is the most-researched CBT protocol implemented in groups. Followup studies have demonstrated the sustainability of profits for 6 months, 1 year, and 2 years posttreatment [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Trauma treatment has been studied at length, and there is significant literature on EBPs for complex and interpersonal trauma (e.g. Bisson et al 2013;Bohus et al 2013;Cusack et al 2016;Foa et al 2013;Gillies et al 2013;Leenarts et al 2013;Syros 2017). However, there are few studies on cultural adaptations of trauma-focused EBPs for the Latinx community, and no studies have been conducted in Latin America (Rivera 2008).…”
Section: Introductionmentioning
confidence: 99%